Extended dissipativity of generalised neural networks including time delays. Issue 11 (18th August 2017) - Saravanakumar, R.; Rajchakit, Grienggrai; Ali, M. Syed; Joo, Young Hoon
ABSTRACT: This article explores the extended dissipativity conditions for generalised neural networks (GNNs) including interval time-varying delays. Extended dissipativity criterions are proposed by making proper Lyapunov–Krasovskii functional. The improved reciprocally convex combination and weighted integral inequality techniques are together applied in main results to establish the new extended dissipativity conditions of delayed GNNs. Finally, the feasibility and superiority of the proposed novel approach is clearly shown by numerical examples.